TINJAUAN PENILAIAN SISTEM INFORMASI REKAM MEDIS RAWAT JALAN DI RUMAH SAKIT JIWA DAERAH Dr. ARIF ZAINUDIN SURAKARTA TAHUN 2022 - Nurhayati Nurhayati; Sri Widodo; Khofifah Nurul Sa’adah (Nusantara Hasana Berdikari, 2022)
Regional Mental Hospital Dr Arif Zainudin Surakarta has an outpatient medical record information system that was implemented in 2019, the system is operated by the registrar, polyclinic, and pharmacy staff. There are still obstacles in managing outpatient medical record data, but the management has never conducted an assessment/evaluation of the system. This study aims to assess the outpatient information system to see the extent to which the user's assessment of the performance of the system. This research is a descriptive study, the object of this research is the Transmedic outpatient medical record information system, the research subjects include registration officers, polyclinic officers, and pharmacy officers. Research instruments in the form of observation guidelines, interview guidelines, and questionnaires. The results of this study are in the aspect of performance that is of good value with an interpretation of the assessment of 69.97%; the information aspect is of good value with 68.91% interpretation of the assessment; the economic aspect is of good value with an interpretation of the assessment of 71.21%; the control aspect has good value with the interpretation of the assessment 71.86%; the efficiency aspect is of good value with an interpretation of the assessment of 67.25%; service aspect with the interpretation of the assessment of 67.03%. The outpatient electronic medical record system is categorized as good and acceptable to respondents